Leveraging the influenza sentinel surveillance platform for SARS-CoV-2 monitoring in Bangladesh (2020–2024): a prospective sentinel surveillance studyResearch in context - Md Ariful Islam; Md Zakiul Hassan; Zubair Akhtar; Saju Bhuiya; Tanzir Ahmed Shuvo; Probir Kumar Ghosh; Asadullah; Md Abdullah Al Jubayer Biswas; Mustafizur Rahman; Mohammad Jubair; Mst Noorjahan Begum; Yeasir Karim; et al. (The Lancet Regional Health - Southeast Asia)
Summary: Background: There is limited global evidence on whether influenza sentinel surveillance platforms can be effectively adapted for long-term SARS-CoV-2 monitoring in low-resource contexts. We explored the utility of the hospital-based influenza sentinel surveillance (HBIS) platform for monitoring SARS-CoV-2 in Bangladesh by comparing SARS-CoV-2 detection in HBIS platform with national COVID-19 platform and assessing how its integration into influenza surveillance aligns with national trends. Methods: From March 2020 to December 2024, we analysed data from patients with severe acute respiratory infection (SARI) and influenza-like illness (ILI) enrolled in HBIS. Socio-demographic and clinical data were recorded, and nasopharyngeal and oropharyngeal swabs were tested for influenza and SARS-CoV-2 using rRT-PCR. Whole-genome sequencing was performed on a subset of SARS-CoV-2–positive samples. Data from national COVID-19 platform were obtained from the Directorate General of Health Services, Bangladesh, and were compared with HBIS platform data using epidemic curves and Pearson correlation analysis. Findings: Among 25,366 (SARI: 20,226; ILI: 5140) patients, 13.0% (3310) tested positive for influenza, 6.6% (1680) for SARS-CoV-2, and 0.2% (43) were co-infected. SARS-CoV-2 positivity in HBIS (6.8%), including 0.2% co-infections, was lower than the national average (13.1%), but showed a strong correlation with national trends (Pearson r = 0.86, P < 0.001). Sequencing of 234 SARS-CoV-2 strains detected the beta and delta variants in April and May 2021, respectively, and omicron subvariants circulating from 2022 to 2024, aligning with the national COVID-19 platform. Interpretation: SARS-CoV-2 positivity trends in HBIS platform closely aligned with the national COVID-19 platform, demonstrating its potential as a sustainable platform for COVID-19 monitoring. Our findings underscore the feasibility of influenza sentinel surveillance as an early warning system for future COVID-19 outbreaks or other respiratory viruses of pandemic concern in Bangladesh and similar settings. Funding: Centers for Disease Control and Prevention (CDC), Atlanta, Georgia, USA (U01GH002259).